Risk Assessment of Onshore Pipeline in Area Gresik - Daniel Mohammad Rosyid; Muhammad Yusuf Jamil; Wahyudi Citrosiswoyo (Department of Ocean Engineering, 2017)
Pipeline is a transport means to distribute the fluid in the form of liquid or gas. Meanwhile, risk is defined as the combination of the likelihood of failure and the consequences of failure. In this research, the implementation of risk assessment using the index or scoring models as developed by Muhlbauer is made. Pipeline used for the analysis was located in Legundi - Cerme, Gresik Area. The pipeline has a diameter of 12 inches which distribute gas. Scoring method is based on a sum index composed of damage indices caused by a third party with a score averagely 57.71, with a score of corrosion index averagely 68, index design with a score averagely 75, and the index operation errors with a score averagely 90. Furthermore, leak impact factor calculation is made by considering leak impact factor consisting of product hazard, leak volume, and dispersion, receptors. Estimates for product hazard criteria score is 7, leak or spill volume is 0.4, the dispersion score is 0.8,and score in receptor variation value of between 10.8 up to 15.9. Relative risk score average obtained from the calculation is 9.87, which is the result of dividing the sum by the leak index impact factor.This low value indicates the pipeline to be classified in the low risk level, or has a sufficiently high safety.